Design of a Cafeteria at Nyabikoni Campus Kabale University. - Tusingwire, Moses (Kabale University, 2023)
A cafeteria is catering place for meals, coffee and tea. This project report is written about the design of a cafeteria that was proposed to be at Kabale University Nyabikoni campus and approved on 11th Nov 2020 by the university panel.This report contents five chapters i.e. Chapter one is the introduction of the project report that states the contents of the background of the project, how the problem was identified and why the project is viable, Chapter two contains the literature review, about architectural design and other working drawings, Chapter three outlines the methodology of how the project was carried out; in there order, Chapter four shows details of the model, budget, and work plan. Chapter five outlines the challenges, recommendations and conclusions, reference and Appendices.